Es la agricultura una respuesta para el crecimiento económico? Un Análisis para el caso de América Latina durante el periodo 1980-2018. - Rivera Flores, Diego David (2023)
Economic growth is one of the most serious problems faced by Latin American contries, which was 2.3% in 2018. Although this has a positive trend, the effect is not significant in the region. This research aims to determine the influence of agricultural productivity on economic growth for 17 Latin American countries, period 1980-2018. The Atlas method was use based on the productive structure of the countries. To consider the impact, panel data econometric techniques and official databases from reliable sources were applied to perform the different tests, considering economic growth as a dependent variable, agriculture as an independent variable, and age-labor population as control variables, fixed capital, technology, water resources and arable land. As part of the methodology, second-generation econometric techniques were used, such as a transversely augmented Dickey-Fuller test (CADF) and transversely augmented IPS (CIPS), which allow controlling the presence of cross-sectional dependency between sections. The main results indicate the existence of a significant impact between agricultural productivity and economic growth. In turn, it is found that there is an equilibrium relationship in the long term between the variables. Finally, the existence of bidirectional causality between agriculture and economic growth was determined. Given this, the policy implications of this research should be focused on agrarian policies and reforms by governments, along with foreign trade regulations and policies, as well as the implementation of taxes on agricultural land. Keywords: Production; Water; Land; Agrarian Policies; Panel data. JEL Classification: E23; Q24; Q25; Q18; C33.